COMMUNICATION DYNAMICS IN SOCIAL SKILLS DEVELOPMENT IN CHILDREN WITH AUTISM IN SCHOOL ENVIRONMENTS - Siti Jubaedah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to describe the dynamics of communication in the development of social skills in children with autism in an inclusive school environment. The research uses a qualitative approach with a case study type. The study subjects consisted of three children with autism, three companion teachers/classroom teachers, and six peers. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model which included data reduction, data presentation, and conclusion drawn, and validated through triangulation of sources and methods. The results showed that the communication patterns of children with autism were dominated by non-verbal and simple verbal communication with limited initiative. The main barriers to social skills development include difficulty understanding spoken language, a tendency to withdraw from crowded social situations, and a lack of peer understanding of inclusive interactions. However, communication strategies based on visual media, teacher mentoring, peer involvement, and positive reinforcement have proven effective in increasing the frequency of children's social interactions. In conclusion, structured communication dynamics and inclusive school environment support are able to significantly promote the development of social skills of children with autism. These findings confirm the importance of collaboration between teachers, peers, and parents to realize a sustainable socialization process in schools.